2019
DOI: 10.1183/23120541.00242-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in health services and medication use among older adults with asthma

Abstract: Sex differences are well documented in chronic disease populations with cardiovascular disease and diabetes. Although recent research has suggested that asthma is more severe in older women compared to men, the extent of this difference remains poorly understood. The objective of this study was to compare rates of asthma-specific health services use (HSU) and medication use, between older women and men with asthma.This population-based cohort study included 209 054 individuals aged ≥66 years with asthma from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Our study also showed that females with severe asthma have a poorer control of symptoms and a higher number of hospitalizations for asthma attacks than males, despite a similar level of FEV1 and a similar rate of severe exacerbations. These data are partially concordant with those reported in other national or international registries on severe asthma: in effect, some studies suggest that females have greater limitations to daily life activities due to asthma 29 30 ; on the contrary, other studies show that males have poorer pulmonary function than females. 12 In our study, the poorer control of asthma symptoms in females compared to males may have been attributed to the higher prevalence of comorbidities (obesity and GERD) in females, which may increase asthma-like symptoms and reduce the efficacy of anti-asthma treatments.…”
Section: Discussionsupporting
confidence: 88%
“…Our study also showed that females with severe asthma have a poorer control of symptoms and a higher number of hospitalizations for asthma attacks than males, despite a similar level of FEV1 and a similar rate of severe exacerbations. These data are partially concordant with those reported in other national or international registries on severe asthma: in effect, some studies suggest that females have greater limitations to daily life activities due to asthma 29 30 ; on the contrary, other studies show that males have poorer pulmonary function than females. 12 In our study, the poorer control of asthma symptoms in females compared to males may have been attributed to the higher prevalence of comorbidities (obesity and GERD) in females, which may increase asthma-like symptoms and reduce the efficacy of anti-asthma treatments.…”
Section: Discussionsupporting
confidence: 88%
“…109 In a Canadian study in adults with asthma aged 66 years and older, women were less likely than men to be prescribed controllers (Figure 2). 97 Contrarily, a real-world study in Italy reported no gender differences in the frequency of ICS or long-acting b-agonist given to patients with asthma when corrected for age and BMI. 59 In terms of OCS use, women are more frequently prescribed OCS for asthma compared with men.…”
Section: Gender Differences In Asthma Treatmentmentioning
confidence: 97%
“…In a Canadian study of health service use among older adults with asthma (aged 66 years and older, mostly urban with a mixed socioeconomic status), women had a higher rate of physician office and asthmaspecific emergency department visits; however, they were less likely than men to receive spirometry and specialist care (Figure 2). 97 The authors hypothesized this may be due to either provider or patient behavior. Similarly, studies showed that women are more likely to engage with their HCP when needed, have an asthma management plan, and regularly use a peak flow meter.…”
Section: Effects Of Sex and Gender On Asthma Treatment And Management...mentioning
confidence: 99%
“…inhaled and systemic corticosteroids and biologics targeted at IL-4, IL-5 and IL-13), which has been shown to be less common in women compared with men [97,98]. This could contribute to poorer control of asthma in women, regardless of treatment and compliance [99], and a more severe clinical manifestation or perception of asthma [100,101].…”
Section: Effectiveness Of Therapiesmentioning
confidence: 99%